Physical and chemical characteristics of seagrass fiber for papermaking - Syed, Nurul Nur Farahin (2013)
Marine angiosperm could inevitably offer considerable potential resources for their fiber yet less research has been conducted especially in Malaysia. In the present study fiber characteristics of seven species of seagrass; Enhalus acoroides, Cymodocea serrulata, big-leaved Halophila ovalis, small-leaved H. ovalis, Halophila spinulosa and Halodule uninervis were investigated. Nine fiber end structure were observed in seagrass fibre including pointed, blunt, scalloped, scimitar-like, spatulate, forked, rounded, one side tapering, and pitted on side. Fiber dimension were studied to determine slenderness ratio, flexibility coefficient, Runkel’s ratio and Luce shape factor species selection. Each species have the tendency in papermaking production as it belong in preferable range of slenderness ratio (>33), Runkel ratio (≤1) and high Luce’s shape factor but low flexibility coefficient characterize by rigid fiber. The chemical composition showed that seven species have high cellulose (>34%) and low lignin content (<20%). Five species were used in papermaking production using Japanese and Western methods excluding small-leaved H. ovalis and H. uninervis due to low dry weight. Enhalus acoroides using both Western and Japanese method has the highest tensile strength with 4.16 kN/m and 3.46 kN/m respectively. The highest breaking length (3.43 km) was observed in T. hemprichii using Japanese method. This showed that both methods were comparable to produce a good quality paper, and only differ in the surface appearance. The papers made from Western method were smoother, while papers made from Japanese method have more aesthetical value.